The Case for Industrial Dualism - Ross, Edward Alsworth (Quarterly Journal of Economics, 1924)
I. The change from handicraft to machine, 384. — II. The intensification of capitalism, 386. — III. Strikes and the sterilization of capital, 387. — IV. Neither cooperation nor socialism possible as a remedy, 390. — V. Existing tendencies lead to capitalistic feudalism, 391. — VI. The alternative is industrial dualism, 393.— VII. Thus can democracy be maintained, capitalistic feudalism averted, 395.